A 12-week rescue therapy by PrOD-based regimen for advanced fibrotic genotype-1 CHC patients who failed to pegylated interferon plus ribavirin. Issue 3 (March 2019) - Wu, Sih-Hsien; Chu, Chi-Jen; Lin, Chung-Chi; Su, Chien-Wei; Lee, Shou-Dong; Wang, Yuan-Jen; Lee, Fa-Yauh; Huang, Yi-Hsiang; Hou, Ming-Chih
Abstract : Background: Treatment of chronic hepatitis C (CHC) evolved rapidly due to the invention of interferon-free direct antiviral agents. Previous clinical trials showed combination therapy with paritaprevir/ritonavir, ombitasvir, and dasabuvir (PrOD) with or without ribavirin (RBV) can cure over 95% of genotype 1 CHC patients, regardless with cirrhosis or not. However, real-world data regarding the efficacy and safety of PrOD-based therapy in Asian HCV genotype 1 CHC patients are limited, especially for advanced-fibrotic patients who failed previous therapy with pegylated interferon (PEG-IFN) plus RBV. Methods: Between January and October 2017, 60 advanced fibrotic (≥F3) genotype 1 CHC patients who failed previous therapy with PEG-IFN and received PrOD-based therapy for 12 weeks were retrospectively enrolled. Weight-based RBV 800 to 1200 mg/d was added for genotype 1b patients with cirrhosis and all genotype 1a patients. Sustained virological response (SVR) was defined by undetectable HCV RNA at the end and 12 weeks after the completion of therapy. Results: The mean age was 63.2 ± 9.3 years, 26 (43.3%) of them were males and 20 (33.3%) were diagnosed to have liver cirrhosis. The mean baseline HCV RNA level was 6.19 ± 0.88 log10 IU/mL and 86.7% (52/60) of patients were infected by HCV genotype 1b. After PrOD-based therapy, the rates undetectable HCV RNA (<15 IU/mL) at week 2, 4, and 12 were 61.7%, 90.0%, and 100%, respectively; 69.6% (16/23) of patients with detectable HCV RNA at week 2 were < 100 IU/mL. Pruritus, fatigue, headache, insomnia, and dizziness were the most common patient-reported adverse events. Grade 2 hyperbilirubinemia were found in 21.6% (13/60) of patients during study period and all belonged to unconjugated hyperbilirubinemia. After posttherapy follow up, all 60 patients (100%) achieved SVR. Conclusion: Our real-world data in Taiwan revealed that PrOD-based rescue therapy is well-tolerated and highly effective for genotype 1 CHC patients with advanced fibrosis failing previous therapy with PEG-IFN plus RBV.